Determination of number, energy and dose albedos of some marbles used in external wall cladding of buildings for 59.54 keV gamma-rays - Yilmaz, D.; Kilic, A. D. (Taylor & Francis Ltd, 2019)
The number , energy and dose albedos were measured at the scattering angle of 168 degrees for 59.54 keV gamma-rays emitted from a radioactive source of Am-241. The experiments were carried out by using an HPGe detector with a resolution of 182 eV at 5.9 keV. Albedo parameters were investigated for cream (C), pink (P), white (W), maroon (M) and green (G) marble samples. The chemical compositions of the marble samples were determined with neutron activation analysis (NAA). It was observed that , and parameters for the pink marble are lower than those of other marble samples. The pink marble has superior shielding capacity than the other marbles.
Keywords: Albedo number; albedo energy; albedo dose; marble